Analysis of 2′-hydroxyflavanone (2HF) in mouse whole blood by HPLC–MS/MS for the determination of pharmacokinetic parameters - Gervazoni, Luiza F. O.; Gonçalves-Ozorio, Gabriella; Ferreira-Paes, Taiana; Silva, Aline C. A.; Silveira, Gabriel P. E.; Pereira, Heliana M.; Pinto, Douglas P.; Cunha-Junior, Edézio F.; Almeida-Amaral, Elmo E. (Frontiers in Chemistry, 2023)
Given the lack of investments, structure, and difficulty of metabolite isolation, promising natural product studies do not progress to preclinical studies, such as pharmacokinetics. 2′-Hydroxyflavanone (2HF) is a flavonoid that has shown promising results in different types of cancer and leishmaniasis. For accurate quantification of 2HF in BALB/c mouse blood, a validated HPLC-MS/MS method was developed. Chromatographic analysis was performed using C18 (5μm, 150 mm × 4.6 mm). The mobile phase consisted of water containing 0.1% formic acid, acetonitrile, and methanol (35/52/13 v/v/v) at a flow rate and total running time of 0.8 mL/min and 5.50 min, respectively, with an injection volume of 20 µL. 2HF was detected by electrospray ionization in negative mode (ESI-) using multiple reaction monitoring (MRM). The validated bioanalytical method showed satisfactory selectivity without significant interference for the 2HF and IS. In addition, the concentration range between 1 and 250 ng/mL showed good linearity (r = 0.9969). The method showed satisfactory results for the matrix effect. Precision and accuracy intervals varied between 1.89% and 6.76% and 95.27% and 100.77%, respectively, fitting the criteria. No degradation of 2HF in the biological matrix was observed since stability under freezing and thawing conditions, short duration, postprocessing, and long duration showed deviations less than 15%. Once validated, the method was successfully applied in a 2HF oral pharmacokinetic study with mouse blood, and the pharmacokinetic parameters were determined. 2HF demonstrated a Cmax of 185.86 ng/mL, a Tmax of 5 min, and a half-life (T1/2) of 97.52 min.